Electron-scattering total cross sections for triatomic molecules: NO2 and H2O - Szmytkowski, Czesław; Możejko, Paweł (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Absolute total cross sections (TCSs) for electron scattering on nitrogen dioxide (NO2) molecules and on water-vapour (H2O) were measured at energies ranging from 3 to 370 eV and 0.5 to 370 eV, respectively. Measurements were carried out using an electron spectrometer with an improved angular and energy resolution. The presented experimental TCS results are at intermediate energies compared with our total cross section estimations based on calculations of elastic and ionization cross sections.
Optica Applicata, Vol. 36, 2006, nr 4, s. 543-550
Keywords: optyka; electron scattering; elastic cross section; ionization cross section; total cross section; nitrogen dioxide; water